2020
DOI: 10.1103/physrevlett.124.041805
|View full text |Cite
|
Sign up to set email alerts
|

Zee-Burst: A New Probe of Neutrino Nonstandard Interactions at IceCube

Abstract: We propose a new way to probe non-standard interactions (NSI) of neutrinos with matter using the ultra-high energy (UHE) neutrino data at current and future neutrino telescopes. We consider the Zee model of radiative neutrino mass generation as a prototype, which allows two charged scalars -one SU (2)L-doublet and one a singlet, both being leptophilic, to be as light as 100 GeV, thereby inducing potentially observable NSI with electrons. We show that these light charged Zee-scalars could give rise to a Glashow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 75 publications
(120 reference statements)
0
27
0
Order By: Relevance
“…This limit is shown by the purple shaded region. A light charged scalar η + 2 /φ + 2 of the model could potentially give rise to a Glashow-like resonance feature [77] in the ultra-high energy neutrino event spectrum at the IceCube; this future IceCube sensitivity is shown by solid brown curve corresponding toan exposure time of 50 ×T 0 . The gray shaded region indicates the current exclusion limit on neutrino magnetic moment from Borexino experiment.…”
Section: Jhep10(2020)040mentioning
confidence: 99%
“…This limit is shown by the purple shaded region. A light charged scalar η + 2 /φ + 2 of the model could potentially give rise to a Glashow-like resonance feature [77] in the ultra-high energy neutrino event spectrum at the IceCube; this future IceCube sensitivity is shown by solid brown curve corresponding toan exposure time of 50 ×T 0 . The gray shaded region indicates the current exclusion limit on neutrino magnetic moment from Borexino experiment.…”
Section: Jhep10(2020)040mentioning
confidence: 99%
“…Non-Standard Interactions in Radiative Neutrino Mass Models Sudip Jana potentially observable NSI with electrons. We show that these light charged Zee-scalars could give rise to a Glashow-like resonance feature [10] in the UHE neutrino event spectrum at the IceCube neutrino observatory and its high-energy upgrade IceCube-Gen2, which can probe a sizable fraction of the allowed NSI parameter space. Within the SM, the only resonance IceCube is sensitive to is the Glashow resonance [11], where electron anti-neutrinos hitting the target electrons in ice could produce an on-shell -boson:…”
Section: Pos(ichep2020)143mentioning
confidence: 91%
“…Next, I discuss a new way [10] to probe NSI of neutrinos with matter using the ultra-high energy (UHE) neutrino data at current and future neutrino telescopes. We consider the Zee model of radiative neutrino mass generation as a prototype [10], which allows two charged scalars -one…”
Section: Ic 2t0mentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [43], it has been also shown that the light charged scalars in radiative models could give rise to a Glashow-like resonance feature in the UHE neutrino event spectrum at the IceCube neutrino observatory and its high-energy upgrade IceCube-Gen2, which can probe a sizable fraction of the allowed NSI parameter space. While the analysis [11,43] is focused on Zee model, it essentially covers various other theoretically motivated models [44,45,46,47,48,49,50,51] with light charged scalars.…”
Section: Towards a Uv Complete Scenariomentioning
confidence: 99%